Physiological-based cord clamping versus immediate cord clamping for infants born with a congenital diaphragmatic hernia (PinC): study protocol for a multicentre, randomised controlled trial : protocol - Horn-Oudshoorn, Emily J. J.; Knol, Ronny; Vermeulen, Marijn J.; Pas, Arjan B. te; Hooper, Stuart B.; Otter, Suzan C. M. Cochius-den; Wijnen, Rene M. H.; Crossley, Kelly J.; Rafat, Neysan; Schaible, Thomas; Boode, Willem P. de; Debeer, Anne; et al. (BMJ open, 2022)
Introduction Pulmonary hypertension is a major determinant of postnatal survival in infants with a congenital diaphragmatic hernia (CDH). The current care during the perinatal stabilisation period in these infants might contribute to the development of pulmonary hypertension after birth—in particular umbilical cord clamping before lung aeration. An ovine model of diaphragmatic hernia demonstrated that cord clamping after lung aeration, called physiological-based cord clamping (PBCC), avoided the initial high pressures in the lung vasculature while maintaining adequate blood flow, thereby avoiding vascular remodelling and aggravation of pulmonary hypertension. We aim to investigate if the implementation of PBCC in the perinatal stabilisation period of infants born with a CDH could reduce the incidence of pulmonary hypertension in the first 24 hours after birth. - Methods and analysis We will perform a multicentre, randomised controlled trial in infants with an isolated left-sided CDH, born at ≥35.0 weeks. Before birth, infants will be randomised to either PBCC or immediate cord clamping, stratified by treatment centre and severity of pulmonary hypoplasia on antenatal ultrasound. PBCC will be performed using a purpose-built resuscitation trolley. Cord clamping will be performed when the infant is considered respiratory stable, defined as a heart rate >100 bpm, preductal oxygen saturation >85%, while using a fraction of inspired oxygen of <0.5. The primary outcome is pulmonary hypertension diagnosed in the first 24 hours after birth, based on clinical and echocardiographic parameters. Secondary outcomes include neonatal as well as maternal outcomes. - Ethics and dissemination Central ethical approval was obtained from the Medical Ethical Committee of the Erasmus MC, Rotterdam, The Netherlands (METC 2019-0414). Local ethical approval will be obtained by submitting the protocol to the regulatory bodies and local institutional review boards. - Trial registration number NCT04373902.